Correlation of QT Dispersion after Exercise Stress-Test with Coronary - Ammann, P.; Bluzaite, I.; Roelli, H.; Korte, W.; Rickli, H.; Brazdzionyte, J.; Urbonaviciene, G.; Zaliunas, R. (Elektronika ir Elektrotechnika, 2004)
The aim of this study was to determine if QTD and heart rate corrected QT dispersion (QTcD) are related to coronary artery disease (CAD). We prospectively assessed QT intervals from electrocardiograms (ECG) at rest and immediately after bicycle stress-test, in 94 patients. In 67 patients (age 62.1 ± 11.7y; 59m/8f) relevant CAD (stenoses > 50%) was assessed. 27 patients (age 61.1 ± 10.2 y; 10m/17f) showed normal coronary arteries. There were no significant differences between patients with or without CAD in QTD at rest. However, QTD (30ms(20-40) vs. 20 ms (5-30); p=0.006) and QTcD (40 ms (23.5-51.5) vs. 29 ms (6.5-38); p = 0.006) assessed immediately after stress-test were significantly longer in CAD. Sensitivity of QTcD to predict CAD (cut off of QTcD ≥ 40 ms) was higher (50.7%) as compared to ST-depression on ECG (38.8%), whereas specificity was lower (74.1% vs. 92.6%). Ill. 4, bibl. 9 (in English; summaries in Lithuanian, English and Russian).